Acute effect of prolactin on the intestinal calcium absorption in normal, pregnant and lactating rats - N. Krishnamra (2018)
Acute effect of prolactin on intestinal calcium absorption was studied in Wistar rats. Prolactin when given subcutaneously 24 h, or intraperitoneally 1 h, before intragastric administration of 45 Ca-containing CaCl 2 solution markedly increased the plasma 45 Ca content. Of interest was the enhancing effect of prolactin on calcium transport seen in 1 h which suggested that prolactin could act directly on the intestine. Physiological significance of prolactin was evaluated in pregnant and lactating rats. Pretreatment with bromocriptine, an inhibitor of prolactin release, had no effect in rats on day 20 of pregnancy but significantly reduced calcium absorption in lactating rats. This reduced calcium absorption was only partially restored by prolactin treatment. The present investigation thus showed that prolactin, besides stimulating 1,25(OH 2 )D 3 production, may also enhance calcium absorption directly. This effect was absent in pregnant rats but was of physiological significance in lactating rats. © 1990.